RANCANG BANGUN PEMBUKA/PENUTUP ATAP PLASTIK DENGAN SENSOR SUHU DAN KELEMBABAN TANAH PADA PEMBIBITAN CABAI MENGGUNAKAN INTERNET of THINGS (IOT) - Ahmad Hilmi; Sulistyanto; Moh. Khotib (Universitas Tarumanagara, 2022)
In nurseries, storage temperature plays a very important role in the quality of cayenne pepper seeds, room temperature affects seed viability, room temperature and humidity can be maintained by adjusting humidity 70-80% at room temperature 20-25ºC. (Fitrianti, 2020). And the condition of the soil that lacks or excess water also affects the lack of nutrients that will be obtained by plants during the rainy season. then a tool was designed entitled